Creating Gender-Responsive Literacy Programs toward Health and Social Security Systems Inclusion of Filipino Migrant Domestic Workers in East Asia - Jocelyn O. Celero; Melissa R. Garabiles; Evangeline O. Katigbak-Montoya (Philippine Institute for Development Studies (PIDS), 2023)
This research aims to examine the gender-responsiveness of the current systems of health care and social protection in the Philippines and East Asia. It also aims to assess the level of health and social security systems literacy of Filipino migrant domestic workers (MDWs) in Hong Kong, Japan, and Singapore, as well as the Philippines. This study resulted in the development of survey tools that included seven measures on the systems literacy of Filipino MDWs. Four of the seven tools were about Philippine government agencies whose mandate includes providing health and social security protection to Filipino MDWs. These agencies are the OWWA, SSS, PhilHealth, and Pag-IBIG Fund. The other three tools focused on the laws and policies regarding health care and social protection to Filipino migrant domestic workers in three destination countries or territories, namely, Hong Kong SAR, Singapore, and Japan. Findings from the interviews with government agencies and NGO leaders in destination areas, as well as pilot surveys, suggest that while still in the destination countries, Filipino migrant domestic workers tend to sometimes disregard Philippine-based programs and policies that seek to protect their health and social welfare. As a result, the level of literacy in Philippine systems fluctuates while the level of literacy in receiving country systems tends to improve the longer Filipino domestic workers live and work in East Asia, gradually alienating them from the Philippine systems. Yet, despite the availability of health and social pension benefits in the receiving context, Filipino domestic workers who are ageing, part-timers, and low-wage may face greater vulnerabilities and barriers to attaining systems literacy compared to other female migrant workers. The study recommends integrating gender into existing policies on health care and social protection to ensure that they match the specific experiences of different categories of female migrant workers. It further suggests that the Philippine government must periodically update and strengthen the promotion of services and programs on various platforms. To raise the level of Filipino MDWs' systems literacy in Philippine health and social security, the government must strengthen awareness of their policies and services, and improve coordination between the Philippine consulates and embassies regarding labour and legal systems in destination countries that may have implications on the portability of health care and social protection programs for OFWs.
Keywords: 330; Philippines; Japan; Singapore; Hong Kong; health security systems; social security systems; systems literacy; gender-responsive